E. J. Lowe and Divine Causal Agency - Ganssle, Gregory (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
In this essay, I apply Lowe’s theory of rational agency to God’s causal activity. I argue that Lowe’s account fits well the traditional notions that God acts in the world for reasons. In contrast to Lowe’s analysis of human causal agency, I argue that in the divine case, reasons for acting are not constituted by needs. They are constituted by God’s desires or plans. The fit between Lowe’s account of causal agency and the contours of divine causal agency motivate an argument in favor of Lowe’s theory. Any philosopher who is a theist ought to think Lowe’s account is likely to be true.